2016
DOI: 10.4330/wjc.v8.i10.575
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity in primary and secondary prevention of cardiovascular disease: Overview updated

Abstract: Although the observed progress in the cardiovascular disease treatment, the incidence of new and recurrent coronary artery disease remains elevated and constitutes the leading cause of death in the developed countries. Three-quarters of deaths due to cardiovascular diseases could be prevented with adequate changes in lifestyle, including increased daily physical activity. New evidence confirms that there is an inverse dose-response relationship between physical activity and cardiovascular disease and mortality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
100
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(108 citation statements)
references
References 90 publications
0
100
0
8
Order By: Relevance
“…A meta‐analysis of 15 prospective cohort and case–control studies in 173 146 participants showed that active commuting involving walking and cycling was associated with an overall 11% reduction in CVD risk 4. Furthermore, exercise as a part of cardiac rehabilitation is a key component for secondary prevention of CVD and the recurrence of MI 5, 6. Physical activity can improve strength and cardiovascular fitness and induce beneficial changes in cardiometabolic risk factors that are independent of mere body weight reduction 7.…”
Section: Introductionmentioning
confidence: 99%
“…A meta‐analysis of 15 prospective cohort and case–control studies in 173 146 participants showed that active commuting involving walking and cycling was associated with an overall 11% reduction in CVD risk 4. Furthermore, exercise as a part of cardiac rehabilitation is a key component for secondary prevention of CVD and the recurrence of MI 5, 6. Physical activity can improve strength and cardiovascular fitness and induce beneficial changes in cardiometabolic risk factors that are independent of mere body weight reduction 7.…”
Section: Introductionmentioning
confidence: 99%
“…In the foreign literature, the issues of pro-health physical activity also comprise the object of numerous studies (Alves et al, 2016;Blair, Kohl, Gordom, Paffenbarger, 1992;Both, 2000;Hupin et. al., 2016;Parsons et al, 2016;Vasconcelos, Cardozo, Lucchetti, Lucchett, 2016;Hart, 2016).…”
Section: Study Resultsmentioning
confidence: 99%
“…Consistent evidence suggests moderate-to-vigorous physical activity decreases the risk of developing cardiovascular disease (Alves et al, 2016;Li & Siegrist, 2012;Palmefors, DuttaRoy, Rundqvist, & B€ orjesson, 2014) and can improve subclinical atherosclerosis (National Heart, Lung, & Blood Institute, 2012). Importantly, there is evidence that physical activity (PA) during adolescence, independent of adult PA, reduces the risk of cardiovascular disease in adulthood.…”
Section: Statement Of Contributionmentioning
confidence: 99%